A Contextual Behavior Science Framework for Understanding How Behavioral Flexibility Relates to Anxiety. Issue 6 (November 2018) - Palm Reed, Kathleen M.; Cameron, Amy Y.; Ameral, Victoria E.
There is a growing literature focusing on the emerging idea that behavioral flexibility, rather than particular emotion regulation strategies per se, provides greater promise in predicting and influencing anxiety-related psychopathology. Yet this line of research and theoretical analysis appear to be plagued by its own challenges. For example, middle-level constructs, such as behavioral flexibility, are difficult to define, difficult to measure, and difficult to interpret in relation to clinical interventions. A key point that some researchers have made is that previous studies examining flexible use of emotion regulation strategies (or, more broadly, coping) have failed due to a lack of focus on context. That is, examining strategies in isolation of the context in which they are used provides limited information on the suitability, rigid adherence, or effectiveness of a given strategy in that situation. Several of these researchers have proposed the development of new models to define and measure various types of behavioral flexibility. We would like to suggest that an explanation of the phenomenon already exists and that we can go back to our behavioral roots to understand this phenomenon rather than focusing on defining and capturing a new process. Indeed, thorough contextual behavioral analyses already yield a useful account of what has been observed. We will articulate a model explaining behavioral flexibility using a functional, contextual framework, with anxiety-related disorders as an example.